PENGARUH KUALITAS PRODUK, BRANDING DAN INFLUENCER MARKETING, TERHADAP MINAT BELI KOSMETIK PADA KONSUMEN PRODUK MISS GLAM DI KOTA BENGKULU - Mutica Apriliya Utami; Merta Kusuma (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the effect of product quality, branding and influencer marketing, on buying interest in cosmetics for consumers of Miss Glam products in Bengkulu City. This type of research is a quantitative approach. The method used in this research is descriptive method. This study uses incidental sampling techniques with a sample size of 120 respondents. The data collection techniques used are interviews, observations, literature studies, and questionnaires. Based on the results of this study and the data analysis described above, it can be concluded that: 1). There is an effect of product quality (X1) on buying interest in cosmetics (Y) at Miss glam Shop Bengkulu City, meaning that the higher the product quality, the higher the buying interest, 2). There is an influence of branding (X2) on buying interest in cosmetics (Y) at Miss glam Shop Bengkulu City, meaning that the higher the perceived quaity, the more buying interest, 3). There is an influence of influencer marketing (X3) on buying interest in cosmetics (Y) at Miss glam Shop Bengkulu City, meaning that the higher the influencer marketing, the more buying interest. 4). There is an effect of product quality (X1), branding (X2) and influencer marketing (X3) together or simultaneously on buying interest in cosmetics (Y).  Key Words: Product Quality, Branding, Influencer Marketing, Purchase Interest, Consumers